2000
DOI: 10.1046/j.1440-1614.2000.00813.x
|View full text |Cite
|
Sign up to set email alerts
|

Community Treatment Orders: relationship to clinical care, medication compliance, behavioural disturbance and readmission

Abstract: CTOs may reduce rehospitalisations by use of depot medication. Earlier and possibly more frequent readmissions in the CTO group shortened the disturbance associated with illness recurrence. It would appear that to establish a control group with equivalent severity of disorder necessary to evaluate the impact of CTOs requires a random allocation design.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

7
76
1
1

Year Published

2003
2003
2023
2023

Publication Types

Select...
7
1

Relationship

0
8

Authors

Journals

citations
Cited by 43 publications
(85 citation statements)
references
References 10 publications
7
76
1
1
Order By: Relevance
“…The CTO also affords the service provider to take action if the patient does not present. These findings are consistent with studies from other jurisdictions that demonstrate increased use of community services for patients on CTOs (Segal and Burgess 2006;Appelbaum 2005;Dawson and Romans 2001;Vaughan et al 2000;Swartz et al 1999).…”
Section: Discussionsupporting
confidence: 90%
See 1 more Smart Citation
“…The CTO also affords the service provider to take action if the patient does not present. These findings are consistent with studies from other jurisdictions that demonstrate increased use of community services for patients on CTOs (Segal and Burgess 2006;Appelbaum 2005;Dawson and Romans 2001;Vaughan et al 2000;Swartz et al 1999).…”
Section: Discussionsupporting
confidence: 90%
“…Many scholars have identified the need to move beyond hospital utilization rates as a measure of efficacy (Dawson et al 2003;Brophy et al 2006;Hunt et al 2007). Some studies have included other outcome measures (Swartz et al 1999;Dawson and Romans 2001;Vaughan et al 2000;Hiday et al 2001). One American study explored the relationship between involuntary outpatient commitment and homelessness, (Compton et al 2003).…”
Section: Literature Reviewmentioning
confidence: 99%
“…The outcomes measures which have been used in the review of success of CMOs in the general community have tended to focus on the use of health services, such as readmission data, length of stay, and outpatient contacts. Vaughan, McConaghy, Wolf, Myhr and Black (2000) also looked at the effect of a Community Treatment Order (CTO) on compliance with medication. They examined CTO outcomes in 123 patients on CTOs in NSW and found that while on CTOs patients receiving depot medications showed high compliance, and significantly reduced readmission rates.…”
Section: Discussionmentioning
confidence: 99%
“…Community treatment orders (CTOs) are used in Australia [9,10] and Canada [6] and give mental health professionals the right to place an individual on an order, whether they are in hospital or not. This is in contrast to extended leave or supervised discharge, which only applies to patients who are being discharged from inpatient care [6].…”
Section: Are We Assessing the Same Intervention?mentioning
confidence: 99%